2015
DOI: 10.1007/s10103-015-1779-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the biochemical changes of tendons of rats in an experimental model of tenotomy under therapeutic ultrasound and LEDs (625 and 945 nm) by near-infrared Raman spectroscopy

Abstract: Given the complexity of the tendon repair process, where the neoformed scar tissue tends to prevent or hamper the tendon from performing its normal functions, ultrasound (US) and light-emitting diode (LED) devices have been applied to modulate the tendon repair process. This study aimed to compare the anti-inflammatory and healing effects of therapeutic US and LED in an experimental model of tenotomy using histomorphometry and Raman spectroscopy. Forty Wistar rats (235 ± 8.3 g) were separated into four groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(62 reference statements)
0
10
0
2
Order By: Relevance
“…Sci. 2020, 21,2150 3 of 12 modifications or mathematical methods for reducing the fluorescence influence (see review [30]) in order to correctly analyse the Raman signal. However, it is also reported that the fluorescence level of tendons increases with age, using traditional biochemical assays [6,26].…”
Section: Resultsmentioning
confidence: 99%
“…Sci. 2020, 21,2150 3 of 12 modifications or mathematical methods for reducing the fluorescence influence (see review [30]) in order to correctly analyse the Raman signal. However, it is also reported that the fluorescence level of tendons increases with age, using traditional biochemical assays [6,26].…”
Section: Resultsmentioning
confidence: 99%
“…This leads us to think that the anti-inflammatory characteristic of the membrane in the ML group was responsible for the result found, since all the experimental groups received the same treatment with of LED. It has been observed that animals treated with LED after tendinous lesions show improvement in inflammatory conditions when compared to non-irradiated animals 29 , 30 . Such effect on inflammation, obtained by LED therapy, is related to increased peripheral microcirculation, modification of membrane potential, resulting in anti-inflammatory effects 29 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Em ensaios clínicos, a evidência do laser para tendinopatia em humanos ainda é escassa, entretanto, Tumilty et al (2015) evidenciaram que fotobiomodulação quando aplicada no espectro eletromagnético do vermelho próximo (660 nm) com potência de 100 mW e energia de 3 J podem promover a redução do processo inflamatório, produzindo metaloproteinases nos tecidos tendinosos durante o processo inflamatório. Moura Junior et al (2015) comprovaram que a fotobiomodulação por LED (625±15 nm; 2 J; 60 s) foi capaz de reduzir o número de células inflamatórias, promovendo a organização, agregação e alinhamento do colágeno nos estágios iniciais da lesão. Confirmando os achados encontrados por Moura-Junior et al (2015), Helrigle et al (2015) concluíram que a fotobiomodulação quando aplicada nos parâmetros de 945 ±10 nm, 3.84 J e 120 s reduziram a liberação de IL-6 e TNF-α e aumentaram a liberação de IL-10, melhorando a inflamação do tendão calcâneo.…”
Section: Discussionunclassified
“…Moura Junior et al (2015) comprovaram que a fotobiomodulação por LED (625±15 nm; 2 J; 60 s) foi capaz de reduzir o número de células inflamatórias, promovendo a organização, agregação e alinhamento do colágeno nos estágios iniciais da lesão. Confirmando os achados encontrados por Moura-Junior et al (2015), Helrigle et al (2015) concluíram que a fotobiomodulação quando aplicada nos parâmetros de 945 ±10 nm, 3.84 J e 120 s reduziram a liberação de IL-6 e TNF-α e aumentaram a liberação de IL-10, melhorando a inflamação do tendão calcâneo.…”
Section: Discussionunclassified